2003
DOI: 10.1200/jco.2003.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Patients 65 Years of Age or Older in Cancer Clinical Trials

Abstract: The elderly are underrepresented in cancer clinical trials relative to their disease burden. Older patients are more likely to have medical histories that make them ineligible for clinical trials because of protocol exclusions. Insurance coverage for clinical trials is one step toward improvement of elderly access to clinical trials. Without a change in study design or requirements, this step may not be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
599
2
17

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 948 publications
(628 citation statements)
references
References 27 publications
10
599
2
17
Order By: Relevance
“…They found that the risk of adverse events was According to recent SEER data from the United States, 65.5% of gastric cancers are diagnosed in patients older than 65 years: the median age at diagnosis of gastric cancer was 71 years and the median age of gastric cancer-related death was 74 years (Ries et al, 2007). However, because elderly patients are generally excluded from cancer chemotherapy clinical trials, data to guide the treatment of older patients with AGC in an evidence-based fashion are lacking (Lewis et al, 2003;Murthy et al, 2004;Trumper et al, 2006;Lichtman et al, 2007b). The recently reported SPIRITS trial and a meta-analysis on first-line chemotherapy in patients with AGC demonstrated a statistically significant benefit in OS for 5-FU-based combination chemotherapy compared with singleagent chemotherapy (Wagner et al, 2006;Koizumi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the risk of adverse events was According to recent SEER data from the United States, 65.5% of gastric cancers are diagnosed in patients older than 65 years: the median age at diagnosis of gastric cancer was 71 years and the median age of gastric cancer-related death was 74 years (Ries et al, 2007). However, because elderly patients are generally excluded from cancer chemotherapy clinical trials, data to guide the treatment of older patients with AGC in an evidence-based fashion are lacking (Lewis et al, 2003;Murthy et al, 2004;Trumper et al, 2006;Lichtman et al, 2007b). The recently reported SPIRITS trial and a meta-analysis on first-line chemotherapy in patients with AGC demonstrated a statistically significant benefit in OS for 5-FU-based combination chemotherapy compared with singleagent chemotherapy (Wagner et al, 2006;Koizumi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, elderly cancer patients often present with concomitant co-morbidities and age-associated physiologic problems, such as impaired organ function and functional changes that make the selection of optimal treatment difficult (Repetto and Balducci, 2002;Lichtman et al, 2007b). There is also uncertainty about the use of systemic palliative chemotherapy in elderly patients because of under-representation of this age group in clinical trials (Murthy et al, 2002;Lewis et al, 2003;Lichtman et al, 2007a).…”
mentioning
confidence: 99%
“…The chance of completing the course of treatment is also lower among these patients [37]. Large randomized trials usually exclude elderly patients with breast cancer, as well as people with comorbidities, thus there is an insufficient evidence for the treatment of such patients [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients frequently are excluded from clinical trials, [13][14][15] such as the 2005 trial by Stupp et al, 16 who investigated the addition of temozolomide to radiotherapy in patients with glioblastoma. Although a few trials since then have included older patients, 17,18 the focus those trials has been on the application of adjuvant therapy after nondefinitive, attempted or completed gross total resection of tumor.…”
Section: Interpretations In the Context Of The Literaturementioning
confidence: 99%
“…Although a few studies have assessed the role of age on the short-term outcome of patients with a primary or metastatic tumors, these had numerous limitations. 7,9,[19][20][21][22] Because patients aged 75 years (and, in some cases, aged 65 years or !70 years) usually or frequently are excluded from most clinical trials, [13][14][15] there is a paucity of data regarding the risk of definitive surgical resection and its correlation with short-term, perioperative outcomes in these patients. Contrary to common assumptions, our analysis of a large, prospective, multi-institutional database suggests that advanced age does not predispose individuals undergoing aggressive surgical therapy for primary or metastatic intracranial tumor to increased risk for operative or short-term postoperative morbidity or mortality.…”
Section: Limitationsmentioning
confidence: 99%